2008
DOI: 10.1128/mcb.00543-08
|View full text |Cite
|
Sign up to set email alerts
|

Ydj1 Protects Nascent Protein Kinases from Degradation and Controls the Rate of Their Maturation

Abstract: Ydj1 is a Saccharomyces cerevisiae Hsp40 molecular chaperone that functions with Hsp70 to promote polypeptide folding. We identified Ydj1 as being important for maintaining steady-state levels of protein kinases after screening several chaperones and cochaperones in gene deletion mutant strains. Pulse-chase analyses revealed that a portion of Tpk2 kinase was degraded shortly after synthesis in a ydj1⌬ mutant, while the remainder was capable of maturing but with reduced kinetics compared to the wild type. Cdc28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 61 publications
2
33
0
Order By: Relevance
“…Since foci are not persistent unless both CaaX proteases are absent, it can be reasoned that there may be CaaX proteins involved in this remodelling event that either directly participate or regulate other proteins in this process. A prime candidate is the chaperone Ydj1p, which is in part found at the ER membrane, where it is involved in ER preprotein translocation and the turnover of proteins, including those subject to ERAD (Caplan et al ., 1992a; Mandal et al ., 2008; Trueblood et al ., 2000; Youker et al ., 2004). Defective post-translation processing of Ydj1p, specifically lack of isoprenylation, disrupts the activation of certain Ydj1p-dependent proteins, so it is possible that a lack of CaaX proteolysis has a similar effect (Flom et al ., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Since foci are not persistent unless both CaaX proteases are absent, it can be reasoned that there may be CaaX proteins involved in this remodelling event that either directly participate or regulate other proteins in this process. A prime candidate is the chaperone Ydj1p, which is in part found at the ER membrane, where it is involved in ER preprotein translocation and the turnover of proteins, including those subject to ERAD (Caplan et al ., 1992a; Mandal et al ., 2008; Trueblood et al ., 2000; Youker et al ., 2004). Defective post-translation processing of Ydj1p, specifically lack of isoprenylation, disrupts the activation of certain Ydj1p-dependent proteins, so it is possible that a lack of CaaX proteolysis has a similar effect (Flom et al ., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In yeast, the ERAD-C substrates are recognized by cytosolic Hsp70 (Ssa1 (Needham and Masison, 2008;Hainzl et al, 2004)) and Hsp40 (Ydj1 (Mandal et al, 2008;Tutar and Tutar, 2008;Wright et al, 2007)) and Hlj1 ncevska-Taneva et al, 2006) chaperones. This is exclusively specific for ERAD-C, and the membrane bound Doa10 (TEB4 in mammals) E3-ligase (Ravid et al, 2006;Kreft et al, 2006), ubiquitinating the substrate protein.…”
Section: Proteinsmentioning
confidence: 99%
“…In particular, since Ydj1-N206, which contains an intact zinc-binding domain (domain II) but not an intact domain I, promoted accumulation of WT levels of Ste11⌬N-K444R protein, whereas little or no Ste11⌬N-K444R accumulated in cells expressing Ydj1-N134, it seems possible that the zinc-binding domain of Ydj1 has a critical role in promoting the accumulation and activity of Ste11 protein. A recent study identified a panel of kinases that accumulate in a Ydj1-dependent manner (Mandal et al, 2008), and it will be interesting to determine whether accumulation and activity of those kinases is dependent on the zinc-binding domain of Ydj1.…”
Section: Role Of Domains I Ii and Iii In Ydj1-client Interactionmentioning
confidence: 99%
“…However, Ydj1 has specific functions in maturation of Hsp90 clients (Johnson and Craig, 2000;Mandal et al, 2008). Unique sequences within the G/F and G/M regions enable Sis1, but not Ydj1, to function in maintenance of the yeast prion, [Rnqϩ] (Yan and Craig, 1999;Lopez et al, 2003).…”
Section: Specificity Of Hsp40 Functionsmentioning
confidence: 99%